PEDAGOGICAL FUNDAMENTALS OF PREPARATION OF STUDENTS FOR INNOVATIVE PROFESSIONAL ACTIVITY - Karimova Mukaddas Otajonvna; Aripov Zoirjon Toirjonovich (International Engineering Journal For Research & Development, 2021)
This article describes the preparation of future preschool teachers for innovative activities, professional issues, specific pedagogical tasks, functional tasks, innovative approaches, innovative technologies.